Extraction of vanadium from high calcium vanadium slag using direct roasting and soda leaching - Li, Xin-sheng; Xie, Bing (International journal of minerals, metallurgy and materials, 2012)
The extraction of vanadium from high calcium vanadium slag was attempted by direct roasting and soda leaching. The oxidation process of the vanadium slag at different temperatures was investigated by X-ray diffraction （XRD）, scanning electron microscopy （SEM）, and energy dispersive spectroscopy （EDS）. The effects of roasting temperature, roasting time, Na2CO3 concentration, leaching tem- perature, leaching time, and liquid to solid ratio on the extraction of vanadium were studied. The results showed that olivine phases and spinel phases in the vanadium slag were completely decomposed at 500 and 800℃, respectively. Vanadium-rich phases were formed at above 850℃. The leaching rate of vanadium reached above 90% under the optimum conditions： roasting temperature of 850℃, roasting time of 60 min, Na2CO3 concentration of 160 g/L, leaching temperature of 95℃, leaching time of 150 min, and liquid to solid ratio of 10：1 mL/g. The main impurities were Si and P in the leach liquor.